THE DEVELOPMENT OF HOTS-BASED MATHEMATICAL PROBLEM USING LOCAL CONTEXT FOR SENIOR HIGH SCHOOL - Agus Susanta; Edi Susanto; Hari Sumardi (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
AbstractOne of the problems that often occur in learning mathematics at school is the difficulty of teachers in providing test instruments. This research aims to develop a valid and practicaly high-level thinking mathematics test instrument for senior high school students in the local context. The higher-order thinking levels that are the focus of this research are analysis, evaluation, and creativity. The type of research conducted is development research using a formative evaluation design. The research instrument consisted of validity sheets and practicality sheets. The validity of the test instrument was analyzed using the Aiken index. The practicality test was carried out in a small group tryout with the subject of the tenth grade of Senior High School in Bengkulu. The study results were high-level thinking math questions in the local context for the tenth grade that were valid and practical, consisting of 5 multiple choice questions with 2 levels of analysis, 2 questions for evaluation, 1 creative question, and 3 essay questions covering all three levels. The study results were high-level thinking math questions in the local context for the tenth grade that were valid and practical, consisting of 5 multiple choice questions with 2 levels of analysis, 2 questions for evaluation, 1 creative question, and 3 essay questions covering all three levels.AbstrakSalah satu permasalahan yang sering terjadi dalam pembelajaran matematika di sekolah adalah sulitnya guru dalam menyediakan instrumen tes. Tujuan dari penelitian ini adalah untuk mengembangkan instrumen tes matematika berpikir tingkat tinggi untuk siswa SMA dalam konteks lokal yang valid dan praktis. Level berpikir tingkat tinggi yang menjadi fokus dalam penelitian ini adalah: analisis, evaluasi, dan kreatif. Jenis penelitian yang dilakukan adalah penelitian pengembangan menggunakan desain formatif evaluation. Instrumen penelitian terdiri dari lembar validitas dan lembar kepraktisan. Validitas instrumen tes dianalisis menggunakan indeks Aiken. Uji kepraktisan dilakukan dalam uji coba kelompok kecil dengan subjek kelas X SMA di Bengkulu. Hasil penelitian berupa soal matematika berpikir tingkat tinggi untuk siswa kelas X SMA konteks lokal yang valid dan praktis sebanyak 5 soal pilihan ganda dengan level analisis sebanyak 2 soal, evaluasi sebanyak 2 pertanyaan, dan kreatif sebanyak 1 pertanyaan serta 3 soal uraian yang mencangkup ketiga level. Soal memenuhi kriteria valid berdasarkan penilaian penguji dan praktis ditinjau dari keterbacaan pada uji kelompok kecil. Hasil uji coba terhadap 24 siswa menunjukkan bahwa sebanyak 14 siswa berada pada kategori sedang (58,33%), 7 siswa pada kategori baik (29,17%), dan 3 siswa pada kategori tinggi (12,50%).